Penggunaan Metode Bercerita Terhadap Keterlambatan Berbicara pada Anak di TK Dharma Wanita Persatuan Provinsi Bengkulu - Randi; Seni Parantika Insani (Yayasan Darussalam Bengkulu, 2024)
The results of the research show that 1) how does the use of the storytelling method affect children's speaking delays in the Dharma Wanita United Kindergarten of Bengkulu Province, as for a) the stages of language development we can observe from the children's fluency in speaking, b) factors that influence children's speaking delays, c) regarding interaction patterns which can be seen in socialization difficulties. 2) what is the parenting style of parents regarding delays in children at the Dharma Wanita United Kindergarten of Bengkulu Province, children are said to have speech development that is not in accordance with children their age. This is influenced by the permissive parenting style that parents apply in caring for and educating children by freeing the child to do everything according to the child's wishes without limits. Parenting patterns have a very big role in causing speech delays in kindergarten children, because a) parents are busy; b) low level of parental education; c) lack of stimulating positive environmental support and interaction; 4) parents' desire for children to be able to speak foreign languages. This reduces the child's experience, knowledge and speaking in the family environment. 4) factors that influence delays in speaking in children at the Dharma Wanita Association Kindergarten of Bengkulu Province, based on the research results that have been obtained are as follows: health factors, neurological factors and structural and physiological factors.